DAYA SAING UMKM INDONESIA - Mahipal, Mahipal (JOURNAL OF BUSINESS STUDIES, 2023)
The competitiveness of micro, small, and medium-sized enterprises (MSMEs) in Indonesia is an important issue that needs to be addressed to enhance their performance and productivity. This study aims to analyze the challenges faced by MSMEs in Indonesia and identify potential solutions to improve their competitiveness. The research methodology used in this study is a literature review that analyzes existing research on the subject. The research findings indicate that MSMEs in Indonesia face several challenges, such as limited access to capital, lack of access to technology, poor product quality, and bureaucratic barriers. To address these challenges, potential solutions are proposed, including improving access to capital and technology, enhancing marketing efforts, improving product quality, and reducing bureaucratic obstacles. These solutions require support from the government and other relevant parties to create a conducive environment for MSMEs to thrive. Enhancing the competitiveness of MSMEs in Indonesia will contribute to national economic growth and improve the welfare of society.